Migraine in perimenopausal women - D. A. Klimentova; G. R. Tabeeva (Неврология, нейропсихиатрия, психосоматика)
Sex hormones have a significant influence on the course of migraine in women. Perimenopause is accompanied by unstable cycle length, vasomotor, urogenital and other symptoms, while the course of migraine usually worsens. In postmenopause ovarian follicular function decreases, and the course of migraine improves in most cases. However, a number of studies have shown that the course of migraine does not change or even worsen after menopause. Perimenopausal and postmenopausal migraine patients are also more likely to suffer from vasomotor symptoms. Hormone replacement therapy is prescribed to relieve vasomotor symptoms, which may worsen the course of migraine. In this review, the influence of perimenopause and postmenopause on the course of migraine, the use of hormone replacement therapy, and methods to relieve and prevent attacks in patients with migraine are examined in detail.